Jeffrey mcmanus' database access with visual basic 6 - McManus, Jeffrey P. ([S.l.] : Sams, 1999)
Database Access with Visual Basic's major emphasis is on solutions, not technology. Rather than rattling off a list of features, diagrams and acronyms, this book provides step-by-step examples of the most important techniques developers typically go through to create database applications. Learn how to design a database, build the user interface, write queries, and construct a three-tiered client server system based on ADO 2.0, RDO, COM, SQL Server or Oracle. Find out "what's new?" in Visual Basic 6 as it applies to data access strategies. Receive more information on different types of SQL queries and differences between the Access and SQL Server dialects.